Exposure to war-related traumatic events, prevalence of PTSD, and general psychiatric morbidity in a civilian population from Southern Lebanon - Dimassi, Hani (2006)
The South of Lebanon has experienced prolonged armed conflict. The current study aims to investigate the degree of exposure to traumatic events and prevalence of posttraumatic stress disorder (PTSD) and nonspecific general psychiatric morbidity in a civilian population from the South of Lebanon. The design was cross-sectional with random sampling. War-related traumatic events and symptoms of PTSD were assessed by the Harvard Trauma Questionnaire and general psychiatric morbidity by the General Health Questionnaire (GHQ-28). Almost all participants, 97.7%, had experienced, witnessed, or heard of a war-related traumatic event. Current PTSD prevalence was 29.3%. PTSD symptoms correlated highly with GHQ-28 symptoms, r = .73 (p < .0001). The present study indicates a need for psychological interventions in the population and studies to assess such interventions.